Cultivating Curiosity: Innovative Strategies for Igniting Student Engagement and Confidence in STEM Education (International Journal of Food and Nutritional Sciences, 2021)
In the face of a rapidly changing world, cultivating curiosity in STEM education is no longer a luxury, but a necessity. Curiosity, the insatiable drive to explore, learn, and understand, is the spark that ignites innovation, fuels problem-solving, and propels individuals to become lifelong learners. Yet, traditional STEM classrooms often prioritize rote memorization and standardized testing, inadvertently extinguishing this vital spark. This paper proposes a paradigm shift, focusing on innovative strategies that educators can employ to cultivate curiosity in their classrooms, transforming STEM learning from a passive process into an active and deeply engaging adventure.